2022
DOI: 10.3390/biom12060790
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Thermodynamic Studies on a Novel Thermotolerant GH10 Xylanase from Bacillus safensis

Abstract: Xylanases have a broad range of applications in agro-industrial processes. In this study, we report on the discovery and characterization of a new thermotolerant GH10 xylanase from Bacillus safensis, designated as BsXyn10. The xylanase gene (bsxyn10) was cloned from Bacillus safensis and expressed in Escherichia coli. The reduced molecular mass of BsXyn10 was 48 kDa upon SDS-PAGE. Bsxyn10 was optimally active at pH 7.0 and 60 °C, stable over a broad range of pH (5.0–8.0), and also revealed tolerance toward dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…[21, 22] and others have been used to produce xylanase. Many parameters, such as temperature, pH, metal ions, detergents and others, affect the activities of xylanase [3, 16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21, 22] and others have been used to produce xylanase. Many parameters, such as temperature, pH, metal ions, detergents and others, affect the activities of xylanase [3, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Many micro-organisms such as Bacillus spp. [3, 7, 12, 13], Aspergillus spp. [14–16], Penicillium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that XYNF1-AS had K m of 7.41 mg mL −1 and k cat of 19.51 min −1 . XYNF1-AS did not display superior catalytic properties compared to known GH10 xylanases (Glekas et al 2022 ; Lafond et al 2011 ; You et al 2019 ).…”
Section: Resultsmentioning
confidence: 95%
“…The temperature coefficient value (Q 10 ) for optimal temperatures of free Xyl, Xyl@ZIF-67, and Xyl@Mn/ZIF-67 was calculated via the following Eq. 2 [35].…”
Section: Determination Of Optimum Temperature and Phmentioning
confidence: 99%